Curcumin suppresses the proliferation and tumorigenicity of Cal27 by modulating cancer‐associated fibroblasts of TSCC. (10th August 2020) - Ba, Pengfei; Xu, Mingcai; Yu, Miao; Li, Linxia; Duan, Xiaoyu; Lv, Shuyan; Fu, Guo; Yang, Jianbo; Yang, Pishan; Yang, Chengzhe; Sun, Qinfeng
Abstract: Cancer‐associated fibroblasts (CAFs) are "activated" fibroblasts in the tumor microenvironment (TME) and play a vital role in all steps of cancer development. Increasing evidence focusing on the function of CAFs suggests that CAFs are candidate therapeutic targets and that drugs targeting the modification of CAFs would suppress tumor progression and be beneficial to tumor treatment and prevention. In the present study, we found that curcumin reversed the phenotype of CAFs to that of peri‐tumor fibroblast (PTF)‐like cells by downregulating the expression of α‐SMA (a special marker for CAFs) and inhibiting the secretion of pro‐carcinogenic cytokines, including transforming growth factor‐β1 (TGF‐β1), matrix metalloproteinases 2 (MMP2), and stromal cell‐derived factor‐1 (SDF‐1). We further demonstrated that the conditioned medium (CM) derived from CAFs promoted the proliferation of Cal27, and this effect was confirmed by the xenograft model. More importantly, we found that curcumin blocked the CAF‐mediated enhancement of Cal27 proliferation in vitro and in vivo. In conclusion, our data suggest that curcumin reverses cell phenotype from CAF to PTF‐like cells and suppresses the CAF‐mediated proliferation and tumorigenicity of Cal27 by inhibiting TSCC CAFs.